2011
DOI: 10.1016/j.ijge.2011.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Age-related Ventricular Remodeling is an Independent Risk for Heart Failure Symptoms in Subjects With Preserved Systolic Function

Abstract: s u m m a r y Background: Age has been shown to be related with increased vascular stiffness, cardiac structural alterations, and geometric remodeling. Data regarding the relationship between clinical heart failure (HF) symptoms and aging-related alterations of ventricular geometries are scarce. We therefore investigated this issue. Methods: We subsequently studied 1,577 participants without cardiovascular or chronic lung disorders. Echocardiography-defined cardiac structures and left ventricular (LV) geometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
2
3
0
Order By: Relevance
“…We did not use this classification in study but increasing BMI itself was found as independent risk factor for RV dilation. Again, in line with our study, it has shown in many studies that several structural and functional cardiac alterations are age-related irrespective of comorbidities (23)(24).…”
Section: Discussionsupporting
confidence: 93%
“…We did not use this classification in study but increasing BMI itself was found as independent risk factor for RV dilation. Again, in line with our study, it has shown in many studies that several structural and functional cardiac alterations are age-related irrespective of comorbidities (23)(24).…”
Section: Discussionsupporting
confidence: 93%
“…We did not use this classification in study but increasing BMI itself was found as independent risk factor for RV dilation. Again, in line with our study, it has shown in many studies that several structural and functional cardiac alterations are age‐related irrespective of comorbidities 26,27 …”
Section: Discussionsupporting
confidence: 92%
“…Again, in line with our study, it has shown in many studies that several structural and functional cardiac alterations are age-related irrespective of comorbidities. 26,27 Although relation between the number of parity and estimated PAP was found statistically significant, there was not any value exceeding 35 mm Hg. Additionally, we did not measure pulmonary artery mean and/or diastolic pressures, therefore we could not diagnose pulmonary hypertension via these measurements.…”
Section: Discussionmentioning
confidence: 79%
“…In the Cardiovascular Health Study, enrolling 5450 healthy individuals aged ≥65 years, hypoalbuminemia was found to be significantly associated with incident HF in 10 years by using propensity matched analysis [ 68 ]. Since the established study reported a significant association between echocardiographic parameters and HF, the impact of SA on cardiac dysfunction should be investigated [ 69 ]. This would not only elucidate the link between SA and HF but also aid early detection of subclinical cardiac dysfunction in healthy individuals.…”
Section: Serum Albumin and Prognosis In Cardiovascular Diseasementioning
confidence: 99%